2022
DOI: 10.3390/pr10122742
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Iron Fluoride and Molten FLiBe

Abstract: The equilibrium potentials of iron in a LiF-BeF2-FeF2 melt were measured using the EMF method and were dependent upon the temperature and iron fluoride concentrations. The empirical equations for the isotherms and equilibrium polytherms of the iron fluoride concentration were obtained. The cathode polarization of iron fluoride in the molten mixture of lithium and beryllium fluoride was measured using the current switch off method from the stationary state. It was found that in the studied temperature and conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…1) is described in detail elsewhere. 37,38 Table III presents the results of the performed measurements. Average arithmetic values of the galvanic element EMF (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) is described in detail elsewhere. 37,38 Table III presents the results of the performed measurements. Average arithmetic values of the galvanic element EMF (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…There is a vast literature data on the measurements of the kind using Li/Li+ and Са/Са2 + dynamic reference electrodes to study the processes in chloride melts, 33,34 as well as К/К + and Ве/Ве 2+ reference electrodes are used to analyze fluoride salts. 28,29,[35][36][37][38] Figure 3 presents a schematic of the electrochemical cell that was used for EMF measurements of the galvanic element.…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that the alteration of the conditional standard potential is compatible with the published literature data. 34 If any single form of chromium cations valence dominates in the melt, we consider the standard state to express the concentration dependence of the cations activity and the equilibrium electrode potentials 36 of the galvanic cell (2). The fluorine ions molar concentration in the fluoride melt equals to unity, therefore, we can conditionally assume that the activity of fluorine ions is equal to one, regardless of the temperature.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the electrolytic cell used in the present research is presented elsewhere. 34 Metallic Cr was added to the electrolyte using the anode dissolution to maintain the desired chromium ions concentration. The amount of electricity passed was calculated from the currenttime dependence and controlled by the inductively coupled plasma mass spectrometry (by the atomic-absorption method using an Optical emission spectrometer with the inductively bound plasma (Perkin Elmer OPTIMA 4300 DV, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The paper by Arkhipov et al [6] provides thermodynamic data for the metal/FLiBe system. These data provide an understanding of the metal behavior in fluoride melts and provide practical guidance when choosing appropriate construction materials to be used in molten salt technologies, as well as for the electrolytic production of metals and the design of molten salt reactors.…”
mentioning
confidence: 99%